Variation of Black Carbon Aerosols on Six Continuous Strike Days of Kathmandu Valley: A Case Study - Sharma, Ram K; Bhattarai, Binod K; Sapkota, Balkrishna; Gewali, Mohan B; Kjeldstad, Berit (Journal of the Institute of Engineering, 2012)
Black carbon (BC) aerosols concentrations were measured using an aethalometer AE 31 at Pulchowk Campus, Institute of Engineering, Lalitpur, Nepal an urban location of Kathmandu valley. The monitoring was conducted from May 2009 to April 2010. In this paper only the data on 30th April (working day) and six continuous strike days (1- 6 May 2010) are analyzed to find out the actual mass of BC aerosols when vehicular and industrial emission was nearly zero. The daily average BC aerosols on these six days are 4.6, 3.0, 7.6, 7.0, 6.1 and 5.5 μg /m3 respectively. Low concentration of BC aerosols in the earlier days is attributed to rain. The decreasing trend in the later days is due to dispersion of collected people from different parts of the country in the valley for the effective operation of strike. It has been found that the average BC aerosols concentration on strike days is (5.6 ± 1.16) μg /m3 while it is (10 ± 4.9) μg /m3 on 30th April, a regular working day. This indicates vehicles and industries emit about 44% of BC in Kathmandu. The average for the month of April, BC comes out to be 12 ± 4.4 μg /m3 showing the contribution from vehicle and industry to be about 55%. Further, it has been observed that the hourly BC aerosols concentration in the strike days does not follow the typical diurnal variation as in the working days. DOI: http://dx.doi.org/10.3126/jie.v8i3.5937 JIE 2011; 8(3): 105-113